Let us denote transpose of a matrix M as M'
A is symetric => A = A'
B is symetric => B = B'
Now AB = BA
take transpose of both and use (AB)' = B' A'
(AB)' = (BA)'
= A'B'
= AB
so (AB)' = AB so AB is symetric
Now to prove the other way
(AB)' = AB = A'B' = (BA)' = (B'A')' = ((AB)')' = AB
so we have proved other way also
so iff holds
2006-09-19 17:05:34
·
answer #1
·
answered by Mein Hoon Na 7
·
1⤊
0⤋
If you have been studying matrices and their transposes, then you probably already have seen the theorem that says
transpose of AB = (transpose of B)(transpose of A) for any n x n matrices A and B.
Now if we know that A and B are symmetric, then by definition transpose of A = A and transpose of B = B, and so by the theorem above, transpose of AB = BA.
Now we are ready to answer your question.
First let's assume that AB = BA. Then, using our previous result. transpose of AB = BA = AB, and so by definition AB is symmetric.
Now we assume that AB is symmetric, i.e. that AB = transpose of AB. Then using the previous result again, we see that AB = transpose of AB = BA.
That should do it. Good luck!
2006-09-19 16:53:12
·
answer #2
·
answered by wild_turkey_willie 5
·
0⤊
0⤋
let C=AB and D = BA
then Cij = AinBnj = AniBjn = BjnAni = Dji
this shows that if A ans B are symmetric then AB is symmetric too
2006-09-19 16:17:00
·
answer #3
·
answered by oracle 5
·
0⤊
0⤋
A is symmetric means a(i,j) = a(j,i)
B is symmetric means b(i,j) = b(j,i)
Write c(i,j) for the elements of AB and d(i,j) for those of BA,
c(i,j) = SUM a(i,k) b(k,j)
d(i,j) = SUM b(i,k) a(k,j)
Note now that
c(i,j) = SUM a(i,k) b(k,j) = SUM b(j,k) a(k,i)
... = SUM d(j,i)
so AB and BA are transposes of each other.
If AB = BA, then AB equals its own transpose, therefore it is symmetric.
2006-09-19 16:12:43
·
answer #4
·
answered by dutch_prof 4
·
0⤊
0⤋
I tried SO HARD to understand what that siad, I break it down and read it slowly... no luck. My math class is just learning that stuff. Good luck! Peace out! Bye. Luv/Kodi
2006-09-19 16:06:52
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋